Association between dental caries risk indicators and various stages of caries in newly erupted permanent teeth - Stošović Kalezić, Ivana; Cvetković, Andrijana; Stevanović, Marko; Martinović, Brankica; Milojković, Zoraida; Mladenović, Raša; Živković, Milan; Djordjević, Nadica; Ivanović, Mirjana (Vojnosanitetski pregled, 2021)
Background/Aim. Identification of caries risk indicators involved in the disease development is of great importance. The aim of this study was to assess the association between distinctive risk indicators and different stages of caries disease process in children. Methods. The cross-sectional study was conducted on a sample (n = 327) of school children ages 7–11. A questionnaire submitted to parents was used to record the data regarding demographic characteristics, children's dietary habits, oral hygiene habits and oral health behaviors. Caries was assessed using the International Caries Detection and Assessment System (ICDAS) II and subjects were stratified according to the highest and most prevalent caries lesion stage. The data obtained were analyzed using the χ2 or Fisher`s exact test and multinomial logistic regression. Results. Caries lesions were detected in 56.6% of examinees observed in the study. Compared to caries-free subjects, appearance of initial caries lesions was statistically significantly influenced by maternal education level (p = 0.021), paternal occupational status (p = 0.023), toothbrushing frequency (p < 0.001), and caries status of deciduous teeth (p = 0.027). Maternal educational level (p = 0.026), paternal occupational status (p = 0.003), sweets and snacks taking frequency (p = 0.005), toothbrushing frequency (p < 0.001), and fluoridate dentifrice usage (p = 0.027) were associated with moderate caries lesions. Maternal educational level (p < 0.001), sweets and snacks taking frequency (p = 0.022) and toothbrushing frequency (p < 0.001) were associated with extensive caries lesions. Maternal educational level (p = 0.02) and brushing frequency (p < 0.001) were statistically significantly associated with the highest prevalence of initial caries lesions. Maternal educational level (p = 0.025), toothbrushing frequency (p < 0.001) and frequency of dental check-ups (p = 0.016) were statistically significantly associated with the highest prevalence of moderate caries lesions. Conclusion. Parental socioeconomic indicators and children's behavior related to oral health were involved in the changes from caries-free status to different caries stages.
Keywords: child; dental caries; habits; oral health; risk factors; socioeconomic factors; surveys and questionnaires